Management of post traumatic cranio vertebral junction instability - Panigrahi, Manas Kumar; Mohan, Beeram Vamsee; Purohit, AK (Indian Journal of Neurotrauma, 2005)
The occipito-atlanto-axial complex is a transition zone between vertebral joint structures and the skull. It is unique in that it allows extensive motion and yet its vertebrae are inter-locked to form an amazingly stable structure. Trauma in this region constitutes to above 25–30% cervical spine injuries. In a retrospective review of 490 cervical spine fractures during a 9-year period, we found 91 fractures involving cranio vertebral junction. Of the 91 patients, 54 had odontoid fractures, 22 had Hangman's fractures, 9 had miscellaneous fractures of C2, 5 had isolated C1 fractures and 1 patient presented with occipito atlantal dislocation. Age, sex, presence of associated injuries, neurological status at admission, treatment, and results of the treatment characterized each case. Excluding two patients who died within the first month of injury and two patients who went against medical advice, follow up data is available for 85 of 91 patients. Two patients were lost to follow up. In all 85 out of 91 patients followed for a median duration of 3.8 years ranging from one week to 8 years. Cranio Vertebral junction trauma constituted about 18.5% of total cervical spinal injuries admitted during this period.Neurological compromise in cranio vertebral junction trauma was noted to be 40.6% in our series. The patients with isolated atlas fractures, stable type I and type III odontoid fractures, hangman's fractures and miscellaneous fractures do well with non operative management.For type II odontoid fractures because of the high nonunion rates associated with non operative treatment, we recommend surgical management with direct anterior odontoid screw fixation within 6 months of injury, and Posterior transarticular screw fixation for fractures after 6 months of injury.The overall patient satisfaction for daily survival was better with surgery and collar as compared to halo.
Keywords: Atlas fracture; Axis fracture; CV junction; Halo stabilization; Hangman's fracture; Odontoid fracture